1997
DOI: 10.1103/physrevb.55.15103
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a strain-induced variation of the magnetic moment in epitaxial Cu/Ni/Cu/Si(100) structures

Abstract: We have studied the magnetic moment and in-plane strain in epitaxial Cu/Ni/Cu/Si͑100͒ structures by varying both the Ni and Cu buffer layer thickness. We find a sharp reduction in magnetic moment with increasing Ni lattice strain. Our structural and temperature-dependent studies exclude interdiffusion, interface roughness, and a decreased Curie temperature as possible causes of the reduced moment, but reveal a strong correlation between the strain and magnetic moment in Cu/Ni/Cu structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
23
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 26 publications
3
23
0
Order By: Relevance
“…The dramatic reduction in M s is consistent with the results of others. 10,24,25 In order to investigate the effects of ion-irradiation quan- ϭ0.978 ergs/cm 2 , K I irr. ϭ0.045 ergs/cm 2 .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The dramatic reduction in M s is consistent with the results of others. 10,24,25 In order to investigate the effects of ion-irradiation quan- ϭ0.978 ergs/cm 2 , K I irr. ϭ0.045 ergs/cm 2 .…”
mentioning
confidence: 99%
“…There have been controversies regarding the origin of the PMA transition: whether magnetoelastic ͑ME͒ effect or interface magnetic anisotropy effects are major factors. [8][9][10][11] Moreover, it has been recently demonstrated that ion irradiation can be used to modify magnetic anisotropy characteristics of thin films from perpendicular to lateral magnetic easy axis. [12][13][14][15] Ion irradiation has been used to modify magnetic properties such as magnetic anisotropy, coercivity, and magnetic exchange fields for well-known PMA systems such as Co/Pt superlattice, Co/Pd, Pt/Co/Pt, Fe/Ag, Fe/Cu, Ni/Pd, and Cu/Ni/Cu.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On one hand, due to the designed matching of the lattice constant, ideal electronic and magnetic properties can be sustained in the thin film [1][2][3] . On the other hand, the existing lattice mismatch can enhance the magnetic moments 4,5 , magnetic anisotropy [6][7][8] , and spin polarization 9 . In both cases, an appropriate choice of the substrate is crucial to stabilize the epitaxial thin films with desired functionalities.…”
Section: Introductionmentioning
confidence: 99%
“…The crystalline structure and domain growth mode of thin metal fi lms can have signifi cant infl uences on the electronic and magnetic structure [1,2,3,4]. Recently, we have studied the altered magnetic [5, 6 and 7], and electronic [5,8,9,10,11], behavior of strained thin fi lms of gadolinium that were obtained by growing Gd on a corrugated Mo(112) substrate, as opposed to W(110) [12], which supports a more 'unstrained' Gd(0001) fi lms.…”
Section: Introductionmentioning
confidence: 99%